Vigabatrin-induced retinal toxicity is partially mediated by signaling in rod and cone photoreceptors. - Jin Yang; Matthew C Naumann; Yi-Ting Tsai; Joaquin Tosi; Deniz Erol; Chyuan-Sheng Lin; Richard J Davis; Stephen H Tsang (PLoS ONE, 2012)
Vigabatrin (VGB) is a commonly prescribed antiepileptic drug designed to inhibit GABA-transaminase, effectively halting seizures. Unfortunately, VGB treatment is also associated with the highest frequencies of peripheral visual field constriction of any of the antiepileptic drugs and the mechanisms that lead to these visual field defects are uncertain. Recent studies have demonstrated light exposure exacerbates vigabatrin-induced retinal toxicity. We further assessed this relationship by examining the effects of vigabatrin treatment on the retinal structures of mice with genetically altered photoreception. In keeping with previous studies, we detected increased toxicity in mice exposed to continuous light. To study whether cone or rod photoreceptor function was involved in the pathway to toxicity, we tested mice with mutations in the cone-specific Gnat2 or rod-specific Pde6g genes, and found the mutations significantly reduced VGB toxicity. Our results confirm light is a significant enhancer of vigabatrin toxicity and that a portion of this is mediated, directly or indirectly, by phototransduction signaling in rod and cone photoreceptors.